1997
DOI: 10.1038/sj.mp.4000325
|View full text |Cite
|
Sign up to set email alerts
|

A novel human myo-inositol monophosphatase gene, IMP.18p, maps to a susceptibility region for bipolar disorder

Abstract: susceptibility region forWe performed a search for new ESTs, sequence tag sites (STSs) and genes in the general area of 18p11.2, bipolar disorder utilizing the transcript database 7 and updates in Uni-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 6 publications
2
46
0
Order By: Relevance
“…IMPA2 is located on chromosome 18 near a region implicated in linkage studies of manic depressive illness (Berrettini et al, 1994;Rojas et al, 2000). IMPA2 produces an mRNA transcript but has been shown to produce IMPase activity (Yoshikawa et al, 1997;Ohnishi et al, 2007). We have recently reported that IMPA2 KO mice have lower kidney inositol levels suggesting that the IMPA2 gene contributes to kidney IMPase activity.…”
Section: Introductionmentioning
confidence: 99%
“…IMPA2 is located on chromosome 18 near a region implicated in linkage studies of manic depressive illness (Berrettini et al, 1994;Rojas et al, 2000). IMPA2 produces an mRNA transcript but has been shown to produce IMPase activity (Yoshikawa et al, 1997;Ohnishi et al, 2007). We have recently reported that IMPA2 KO mice have lower kidney inositol levels suggesting that the IMPA2 gene contributes to kidney IMPase activity.…”
Section: Introductionmentioning
confidence: 99%
“…Three of the promoter variants (À241_À237dup, À207T4C and À185A4G) are present in a region of alternative transcription start sites, 12,13 where À241_À237dup represents the five first nucleotides of the transcript reported by Yoshikawa et al 29 The À207T4C polymorphism is localized in a putative MZF1 regulatory site. 28 There is some evidence for altered IMPase enzyme activity 21 and changes in the IMPA2 expression levels 23 in bipolar patients compared to control individuals.…”
Section: Impa2mentioning
confidence: 99%
“…12 Recently, a gene on chromosome 18p11.2, named IMPA2, was predicted to encode an IMPase of high similarity to the IMPA1-encoded protein, especially in the active site and the ion-binding regions. 12,13 However, the IMPA2-encoded protein has not yet been isolated or functionally characterized.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Two genes encoding human IMPases have been identified: IMPA1 and IMPA2. IMPA2 was proposed as a plausible candidate gene by Yoshikawa et al, 10 because of its location within a region of positive linkage findings to BP 14,15 and the possible functional role of the inositol phospholipid signalling system. Yoshikawa et al 16 reported that the group of haplotypes containing either À185A, 97-15G or 558C have significantly higher frequencies in schizophrenics, but not in bipolar disorder patients from Japan.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Myo-inositol monophosphatase 2 (IMPA2) codes for a second human myo-inositol monophosphatase. The gene has been mapped to chromosome 18p11.2 10 and its structure has been characterized. 11,12 The gene is a potential biochemical target for the action of lithium.…”
Section: Introductionmentioning
confidence: 99%